2009
DOI: 10.1111/j.1399-3054.2009.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal temperature favors reserve formation in biennial carrot (Daucus carota) plants

Abstract: In response to suboptimal temperatures, temperate annual plants often increase root:shoot ratios, build-up carbohydrates and display typical morphological and anatomical changes. We know less about the responses of biennials such as carrot. As a model plant, carrot has the additional feature of two functionally and morphologically distinct root parts: the taproot, which stores carbohydrate and other compounds, and the fibrous root system involved in acquisition of water and nutrients. Here, we analyze the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…Stewart et al (2016) showed that higher photosynthetic capacities in cool-grown vs hot-grown A. thaliana ecotypes from Sweden and Italy were associated with greater numbers of phloem cells in foliar veins, and that the lower transpiration rates in these cool-grown plants were associated with fewer xylem cells in foliar veins when compared with hot-grown plants (see also Adams et al 2016). These observations are consistent with reports of greater phloem-to-xylem ratios in cold-grown leaves of spring and winter wheat (Equiza and Tognetti 2002) and in the vasculature of carrot root (González et al 2009). Another previous study ) characterized plants grown under a range of conditions, but did not address phloem-to-xylem ratios.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Stewart et al (2016) showed that higher photosynthetic capacities in cool-grown vs hot-grown A. thaliana ecotypes from Sweden and Italy were associated with greater numbers of phloem cells in foliar veins, and that the lower transpiration rates in these cool-grown plants were associated with fewer xylem cells in foliar veins when compared with hot-grown plants (see also Adams et al 2016). These observations are consistent with reports of greater phloem-to-xylem ratios in cold-grown leaves of spring and winter wheat (Equiza and Tognetti 2002) and in the vasculature of carrot root (González et al 2009). Another previous study ) characterized plants grown under a range of conditions, but did not address phloem-to-xylem ratios.…”
Section: Introductionsupporting
confidence: 92%
“…The comprehensive dataset presented here revealed significant linear positive correlations between all features of xylem anatomy and transpiration rate and between all features of phloem anatomy and photosynthetic capacity across all growth environments despite contrasting acclimation trends to growth light intensity vs growth temperature. Our findings that foliar xylem and phloem features can be adjusted to specific environmental conditions both differentially (increased minor-vein xylem-to-phloem ratio in response to high vs low growth temperature) and in parallel (concomitant increase in minor-vein xylem and phloem in response to high vs low growth light intensity) in a winter annual are consistent with shifts to a greater phloem-to-xylem ratio in response to low growth temperature in spring and winter wheat leaves (Equiza and Tognetti 2002) and in carrot root (González et al 2009) as well as with greater numbers of both phloem and xylem cells in response to high light intensities in kiwifruit (Biasi and Altamura 1996). The absence of correlations between photosynthesis and foliar xylem features in A. thaliana across the entirety of growth conditions used here was driven by the upregulation of photosynthetic capacity in this winter annual under a cool growth regime that did not lead to concomitant increases in xylem features.…”
Section: Acclimation Of Photosynthesis and Foliar Phloem Anatomy Can mentioning
confidence: 63%
“…The involvement of Suc in phloem differentiation in in vitro grown plants was showed many decades ago 81 and accordingly, it has been found that conditions that favor Suc accumulation also induce the development of phloem parenchyma (which is the most important sink for assimilates) in carrot roots. 82 In agreement with the role of promoting reserve structures formation, Suc has been found to induce the development of storage organs in different species. The most well-known case is that of potato tuber induction.…”
Section: Sucrose Signaling In Plant Developmentmentioning
confidence: 59%
“…Soil temperature plays a significant role in plant growth and development; nonetheless, the effect of temperature is often implicitly presumed to be correlated with air, but not soil temperature. Recently, it has been reported that soil temperature more closely associates with crop development than air temperature (Sabri et al, 2018; González et al, 2009), so that plant growth is visibly affected by changes in soil temperature (Gan et al, 2013; Pramanik et al, 2015). From the results, we found that the effect of wheat straw mulch on soil temperature was more pronounced during the early stages of growth (V4 and R2 growth stages), because of the sparse crop cover compared to later growth stages (Fig.…”
Section: Discussionmentioning
confidence: 99%